Sub-10-nm-sized Au@AuxIr1-x metal-core/alloy-shell nanoparticles as highly durable catalysts for acidic water splitting - Wang, Huimin (2024)
The absence of efficient and durable catalysts for oxygen evolution reaction (OER) is the main obstacle to hydrogen production through water splitting in an acidic electrolyte. Here, we report a controllable synthesis method of surface IrOx with changing Au/Ir compositions by constructing a range of sub-10-nm-sized core-shell nanocatalysts composed of an Au core and AuxIr1-x alloy shell. In particular, Au@Au0.43Ir0.57 exhibits 4.5 times higher intrinsic OER activity than that of the commercial Ir/C. Synchrotron X-ray-based spectroscopies, electron microscopy and density functional theory calculations revealed a balanced binding of reaction intermediates with enhanced activity. The water-splitting cell using a load of 0.02 mgIr/cm2 of Au@Au0.43Ir0.57 as both anode and cathode can reach 10 mA/cm2 at 1.52 V and maintain activity for at least 194 h, which is better than the cell using the commercial couple Ir/C‖Pt/C (1.63 V, 0.2 h).